Desigualdades Sociais e Acesso Seletivo ao Ensino Superior no Brasil no Período 1994-2001 - Jorge C. R. da Silva Mello (Universidad Autónoma de Madrid, 2018)
Higher education in Brazil has been experienced a process of expansion, which began in the mid 90's. The increase in the number of admissions has started over, after a period of stagnation in the previous decade, and has increased even more after 1997. This has occurred in a context of increase in upper secondary graduation and under the effects of public policies to make the enlargement of the system feasible. The private sector was the main responsible in the expansion process, due to reduction of legal restrictions for the creation of new institutions and courses. This research examines the relations between both the admission opportunities and the drop out risks and some of the student's socioeconomic and family characteristics in this recent expansion context in Brazil. The analysis uses a regression model based on data from Brazil's Monthly Employment Survey (PME) from 1994 to 2001. The results suggest that both the admission and drop out are highly affected by the social conditions of the students, that the admission chances were reduced for the upper secondary graduation and that the drop out risks remained constant. Also, the effect of social background on educational inequalities did not suffer modifications in the period.